2019
DOI: 10.1126/scitranslmed.aat9321
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of the RB1 pathway in retinoblastoma with the oncolytic adenovirus VCN-01

Abstract: Retinoblastoma is a pediatric solid tumor of the retina activated upon homozygous inactivation of the tumor suppressorRB1. VCN-01 is an oncolytic adenovirus designed to replicate selectively in tumor cells with high abundance of free E2F-1, a consequence of a dysfunctional RB1 pathway. Thus, we reasoned that VCN-01 could provide targeted therapeutic activity against even chemoresistant retinoblastoma. In vitro, VCN-01 effectively killed patient-derived retinoblastoma models. In mice, intravitreous administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 57 publications
(81 reference statements)
0
55
0
2
Order By: Relevance
“…Other viral vectors for retinoblastoma gene therapy induce an oncolytic effect, such as the adenoviruses H101 (Song et al, 2010) and Ad-TERT p-E1 (Wang et al, 2013), which have been tested in preclinical studies. Currently, the most advanced oncolytic adenovirus for retinoblastoma is VCN-01, designed to replicate selectively in tumor cells with high abundance of free E2F-1 transcription factor activity due to the dysfunctional RB1 pathway (Pascual-Pasto et al, 2019). The genome of VCN-01 contains one deletion in the E1A gene that precludes viral replication in RB1-functional cells and one insertion of an E2F1 promoter under the E1A gene that favors replication in cells with free E2F-1 (Rodriguez-Garcia et al, 2015).…”
Section: Gene Therapymentioning
confidence: 99%
“…Other viral vectors for retinoblastoma gene therapy induce an oncolytic effect, such as the adenoviruses H101 (Song et al, 2010) and Ad-TERT p-E1 (Wang et al, 2013), which have been tested in preclinical studies. Currently, the most advanced oncolytic adenovirus for retinoblastoma is VCN-01, designed to replicate selectively in tumor cells with high abundance of free E2F-1 transcription factor activity due to the dysfunctional RB1 pathway (Pascual-Pasto et al, 2019). The genome of VCN-01 contains one deletion in the E1A gene that precludes viral replication in RB1-functional cells and one insertion of an E2F1 promoter under the E1A gene that favors replication in cells with free E2F-1 (Rodriguez-Garcia et al, 2015).…”
Section: Gene Therapymentioning
confidence: 99%
“…Warner et al demonstrated that early expression of hNIS in colon cancer cells made viral replication reliably imageable via positron emission tomography (PET) of I-124 uptake (45). Direct intratumoral injection of oncolytic adenovirus VCN-01 for the treatment of retinoblastoma has also been shown to be effective (46). Choi et al proved that CF33 (a novel chimeric orthopoxvirus encoding luciferase, enabling real-time view of cell infection), was effective in vitro with potent cytotoxicity and efficient intracellular replication observed in triple-negative breast cancer (TNBC, an aggressive subtype of breast cancer with high recurrence rate and poor prognosis) lines with PI3K/AKT pathway mutations (47).…”
Section: Direct Intratumoral Deliverymentioning
confidence: 99%
“…Thus, blindly increasing the application concentration of the virus to compensate for its lack of selectivity will inevitably increase the public concern about the safety of oncolytic virotherapy. Requires highly selective tissue targets (55) Absorbed slower than intravenous injection (65) Limited to central nervous system tumors (68) Applied only to small animals in which veins are difficult to find (65) Complex procedures make repeat dosing difficult (61,63) Physiological barriers such as blood-brain barrier and oncolytic virus elimination by the immune system (55) Mostly applied in vitro experiments (39,42,(44)(45)(46)(47) This route of administration, if any, would be the most likely to lead to toxicity (65) Additionally, those considering use of intravenous administration of an oncolytic virus also need to consider the existence of physiological barriers, such as blood-brain barrier, and the elimination of oncolytic virus by the immune system (55). Is it possible that a wide variety of oncolytic viruses can bypass the blood-brain barrier?…”
Section: Other Routes Of Deliverymentioning
confidence: 99%
“…VCN-01 is an OAd expressing PH20 hyaluronidase [155], PH20 hyaluronidase can promote the spread of OVs between tumor cells by degrading the ECM. VCN-01 has now entered clinical trials for the treatment of pancreatic adenocarcinoma and retinoblastoma [156].…”
Section: Ecm-degrading Enzymesmentioning
confidence: 99%